ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN SMARTPHONE: STUDI KASUS: SISWA/I SMKS BUDI AGUNG - Isra Rafika Sihombing (Jurnal Bina Bangsa Ekonomika, 2024)
The purpose of this study was to analyze the factors that influence the demand for smartphone case studies in students / I SMK S Budi Agung Medan using descriptive statistical analysis. The sample used in this study was 120 students of SMKS Budi Agung Medan. Variables are measured using the Likert scale (1 = strongly disagree; 5 = strongly agree). Variable factors - Smartphone demand factors are price, income, number of family members and tastes. The results of the analysis of price, income and taste are the variables that have the greatest influence on smartphone demand. While the number of family members is an influential variable in the demand for smartphones of students / I SMK S Budi Agung Medan